Third-Party Monitoring of Initial Environmental Examination (IEE) Implementation on Sand, Gravel, and Stone Extraction in Nepal - Khanna, Sabita Aryal; Karki, Suraj; Sigdel, Ek Raj (Kathmandu University Journal of Science, Engineering and Technology, 2024)
The wise use of natural resources can help boost development. IEE (Initial Environmental Examination) is a tool used to check and balance environmental disorders (EPA, 1996). With the enactment of Local Self-Governance Act, 1999, district development committees have been given responsibilities to formulate and implement programs related to the use and protection of natural resources for the development of their area. This paper is an attempt to study the scenario of IEE implementation in developmental projects in four districts namely Sarlahi, Sindhuli, Arghakhanchi, and Kapilvastu. The different parameters like baseline, compliances, impact, physical, biological, and socio-economic and cultural aspects are assessed by use of the monitoring format developed under national EIA Guidelines 1993 and Environmental Protection Regulation 1998.Compliance monitoring in sand and gravel extractions projects are highly complied in hilly districts as compared to Terai districts. Out of twenty-six parameters taken for the study purpose, only seven parameters are not complied in all sand excavation projects, twelve parameters are not found complied in more than four sand, gravel, and boulder extraction projects in the study area. However, the poorest condition is found at Lakhandehi river of Sarlahi district where only two parameter are found complied. Mitigation measures of all project sites are planned and allocated the costs, however, the implementation level is found very poor. Only few activities like protection work for small irrigation canals, earthen roads, and cross over are made in Arghakhanchi and safety measures in Sindhuli districts are implemented. Amount of extraction of river sediments is found greatest in Bagmati River, which is also larger than the other rivers. The extraction in Sukwel and Mainar river of Kapilvastu district are closed due to the ban imposed by the court until further notice. Continuous monitoring and strictness by authority are needed for proper implementation of IEE promises.